Enhanced Chemical Stability of Ag Nanowires by Slight Surface Modification with Pd. Issue 13 (4th May 2018) - Song, Jun Hyuk; Kim, Young‐Tae; Seol, Jae‐Bok; Park, Chan‐Gyung; Myoung, Jae‐Min; Jeong, Unyong
Abstract: The chemical stability of Ag nanowires (NWs) can be addressed by introducing a layer of noble metal alloy, in particular Ag–Pd alloy, on the Ag NW surface. Due to the high cost of noble metals, it is practically important to use the least amount of noble metals as possible while achieving the chemical and electrical properties required for the electrode. To minimize the amount of Pd added to Ag NWs, the electrode performance should be correlated with the elemental distribution of Pd in the Ag NW. In this study, the amount of Pd deposited on Ag NWs is varied and the 3D elemental distribution of Pd is characterized using atom probe tomography (APT). The results indicate that chemical stability against oxidation can be achieved when the surface layer contains a very small amount of Pd (≈5 at%), thereby maintaining the good electrical and mechanical properties of the pristine Ag NW electrode. This study demonstrates the suitability of Pd‐treated Ag NWs as electrodes for electro‐chemiluminescence involving corrosive oxidation reactions. Abstract : The galvanic replacement between Pd and Ag nanowires (NWs) is carefully controlled and the 3D elemental distribution of Pd‐treated NWs is characterized using atom probe tomography (APT). The results indicate that chemical stability of the Ag NWs can be enhanced with a very small amount of Pd. The suitability of Pd‐treated Ag NWs is demonstrated by electro‐chemiluminescence (ECL).